The Influence of Principal's Supervisory Competence in Improving the Quality of Education - Fauzi, Helmi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
This research aims to see the influence of the principal's leadership on improving school quality at MAN Cililin. In addition, this research was conducted to examine and measure how much significant influence the school principal's leadership role has on the quality of education. This research was carried out at MAN Cililin with quantitative research. This research method uses a descriptive survey method with correlation analysis to see the relationship between the independent variables, namely the leadership of the school principal, and the attachment variable, namely the quality of education in schools. The population of this research is school teachers at MAN Cililin with a sample of 31. This research instrument uses questionnaires and interviews which have been tested for validity and reliability. The specifications for data analysis requirements used consist of a normality test using Kolmogorov Smirnov and a linearity test with the hypothesis used, namely correlation and regression tests using SPSS version 26. In this study, it can be concluded that the principal's leadership and the quality of education at the MAN Cililin school have a very strong relationship. strong with a correlation coefficient value of 0.907. Apart from that, it was found that the principal's leadership had an influence of 81.2% on the quality of education in schools and the remaining 18.8% was influenced by external factors with the regression equation model Y = 18.117 + 0.658X. Thus, for further research, research can be carried out to see the differences, correlations, and interactions that occur in student learning outcomes at MAN Cililin based on the cognitive level and gender of students to compare with other schools.